A Representação Do Trauma No Romance Gráfico El Arte De Volar - Silveira, Daisy Mota Da [UNIFESP] (2018)
Among The Conflicts That Occurred During The First Half Of The Twentieth Century, The Spanish Civil War Was, And Still Is, One Of The Most Violent Events That Generated A Trauma That Has Been Lasting 80 Years. El Arte De Volar, By Antonio Altarriba And Kim, Released In 2009, Is An Example Of The Effects Of Silence And Forgetfulness On The Lives Of Those Who Participated Actively In That Period And Who Saw Their Country And Identity Erased By The Totalitarian State Created By Franco. As A Way To Overcome The Pain Caused By His Father's Suicide, The Author Transformed It Into Art By Reconstructing The Past In The Form Of A Graphic Novel. With Its Fragmented, Plastic And Artistic Structure, This Work Presents Antonio Lope's Life In Order To Search And Make A Transmission Movement For A Legacy That Needs To Be Rescued. Thus, This Work Aims To Analyze The Representation Of Traumatic Memory Through The Graphic Novel El Arte De Volar, Narrative Strategies, And The Construction Of The Narrative Identity Of An Individ